Docstoc

HOG-Processing

Document Sample
HOG-Processing Powered By Docstoc
					                Dx = (−1 , 0 , 1)

              Dy = (−1 , 0 , 1)T

                        I



Ix = I ∗ Dx
Iy = I ∗ Dy
             ￿ 2    2
    | G |=    Ix + Iy

            Iy
θ = arctan( Ix )
[0 , 40 )



   [40 , 80 )



  [80 , 120 )
v                       ￿ v ￿k   ε




    v → v/(￿ v ￿1 +ε)
          ￿
    v → v/ ￿ v ￿2 +ε2
                2
          (4 × 8) × (2 × 2) × 9 = 1152




                {xk , yk } ∈ χ × {−1 , 1}   xk
     yk
xk                        φ
           f (x) = w · φ(x) + b   f (x)
        φ(xi )                            x
f (x)
yi , i = 1, . . . , n


                             Hi




                                 ￿ n
               ˆ            1                                 D2 [y, yi , Hi ]
               f (y) =                | Hi |−1/2 t(wi ) exp(−                  )
                         n(2π)3/2 i=1                               2
                                   D2 [y, yi , Hi ] = (y − yi )￿ Hi−1 (y − yi )

                                                        y      yi                  t(wi )




                   ￿ n
 ˆ            1                −1/2    −1                       D2 [y, yi , Hi ]
∇f (y) =                | Hi |      Hi (yi − y)t(wi ) exp(−                      )=
           n(2π)3/2 i=1                                               2
                              ￿ n                                                     ￿
                       1       ￿                                    D2 [y, yi , Hi ]
                          3/2
                                    | Hi |−1/2 Hi−1 yi t(wi ) exp(−                  ) −
                   n(2π)        i=1
                                                                            2
                                            ￿￿ n                                                     ￿ ￿
                                     1         ￿                                   D2 [y, yi , Hi ]
                                        3/2
                                                   | Hi |−1/2 Hi−1 t(wi ) exp(−                     ) y
                                 n(2π)         i=1
                                                                                         2

       ￿i

                                                                           2
                                        | Hi |−1/2 t(wi ) exp(− D [y,yi ,Hi ] )
                                                                    2
                              ￿i (y) = ￿
                                       n                           2 [y,y ,H ]
                                          | Hi |−1/2 t(wi ) exp(− D 2 i i )
                                         i=1

                    ￿
                    n
                          ￿i = 1
                    i=1




                                          n
                                                               ￿ n                     ￿
                             ∇f (y) ￿
                               ˆ                                ￿
                                   =  ￿i (y)Hi−1 yi −                     ￿i (y)Hi−1       y
                              ˆ
                             f (y)       i=1                        i=1




                                                       n
                                                       ￿
                                           −1
                                          Hh (y) =           ￿i (y)Hi−1
                                                       i=1
                                                                                         Hi



                                                          ￿ n              ￿
                                            ˆ
                                          ∇f (y)           ￿
                                m(y) = Hh        ≡ Hh (y)     ￿i (y)Hi−1 yi − y
                                          fˆ(y)
                                                                       i=1

                                                    ˆ
                                                   ∇f (y) = 0                 m(y) = 0



                                                           ￿   n
                                                                                     ￿
                                                               ￿
                                          ym = Hh (ym )              ￿i (y)Hi−1 yi
                                                               i=1

                                 yi                   ym
                                                                                                           yi , i =
1, . . . , n         ym



                              Hi Hi                                                           diag [Hi ]




                                             ￿                                            ￿
                                 diag [Hi ] = (exp (si ) σx )2 , (exp (si ) σy ) , (σs )2

               σx , σy , σs
                       #f alseN egatives
M issRate =    #trueP ositives+#f alseN egatives




                       #trueP ositives
P recision =   #trueP ositives+#f alseP ositives
#f alseN egatives

#trueP ositives

#f alseP ositives




                                              ao   bp
              bgt


                           area (bp ∩ bgt )
                    ao =
                           area (bp ∪ bgt )




                                       ao
area (bp ∩ bgt ) = (396 − 305) × (411 − 127) = 91 × 284 = 25844
area (bp ∪ bgt ) = (443 − 259) × (458 − 90) = 184 × 368 = 67712


       25844
ao =   67712
               = 0.38

				
DOCUMENT INFO
Categories:
Tags:
Stats:
views:3
posted:1/10/2011
language:Albanian
pages:47